2010
DOI: 10.1038/ncomms1001
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 improves healthy ageing and protects from metabolic syndrome-associated cancer

Abstract: Genetic overexpression of protein deacetylase Sir2 increases longevity in a variety of lower organisms, and this has prompted interest in the effects of its closest mammalian homologue, Sirt1, on ageing and cancer. We have generated transgenic mice moderately overexpressing Sirt1 under its own regulatory elements (Sirt1-tg). Old Sirt1-tg mice present lower levels of DNA damage, decreased expression of the ageing-associated gene p16 Ink4a , a better general health and fewer spontaneous carcinomas and sarcomas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
416
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(440 citation statements)
references
References 42 publications
18
416
0
6
Order By: Relevance
“…In addition, we observed an overall decline in the physiological condition of SirT7 −/− mice, including reduced circulating IGF‐1 protein, increased p16INK4 expression, altered HSC compartment, and leukopenia (Fig 2D–H). SIRT1 overexpression in mice results in a delayed onset of age‐related pathologies that correlate with reduced p16INK4 expression (Herranz et al , 2010). Progeroid mouse models, including SirT6 −/− mice (Mostoslavsky et al , 2006), display a systemic reduction in IGF‐1 levels, which might be related to the optimization of energy resources in response to cellular stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed an overall decline in the physiological condition of SirT7 −/− mice, including reduced circulating IGF‐1 protein, increased p16INK4 expression, altered HSC compartment, and leukopenia (Fig 2D–H). SIRT1 overexpression in mice results in a delayed onset of age‐related pathologies that correlate with reduced p16INK4 expression (Herranz et al , 2010). Progeroid mouse models, including SirT6 −/− mice (Mostoslavsky et al , 2006), display a systemic reduction in IGF‐1 levels, which might be related to the optimization of energy resources in response to cellular stress.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 transgenic mice (SIRT1Tg mice) were a gift from Manuel Serrano. 5 The animals were killed, and the tissues were recovered and stored at − 80°C. All of the methods employed in this study were in accordance with the Guide for the Care and Use of Laboratory Animals published by the U.S. National Institutes of Health (NIH Publications No.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Herranz and colleagues showed that transgenic animals overexpressing SIRT1 are protected against diethylnitrosamine/high fat dietinduced liver carcinogenesis compared with nontransgenic controls (27). The protective effect was explained, in part, by SIRT1-mediated regulation of NF-kB activity; SIRT1 overexpression reduced NF-kB-mediated inflammation and hepatic cell malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…40). However, it still needs to be determined if SIRT1 overexpression is indeed an initiating event, as no tumors were reported to be induced in SIRT1 overexpressing transgenic mice, in fact, these mice had fewer spontaneous carcinomas and sarcomas (27,41). Further investigations may reveal that as important as SIRT1 overexpression is, perhaps equally important is loss of expression of other family members, for example SIRT3 and SIRT6 in promoting tumor growth in HCC.…”
Section: Discussionmentioning
confidence: 99%